Visages de la bergère dans les broadside ballads - Chantal Schütz (Etudes Epistémè)
Broadside ballads represent one of the material traces of the penetration of the pastoral mode in all social classes. Three types of pastoral broadside ballads are discussed : elegies, dialogues and comedic songs, revealing how the multimodal nature of the broadsides (text, image, music) makes possible a limited representation of the material conditions of shepherds’ lives. The image of shepherdesses that emerges from those texts involves agency and a distinct voice, and characters that are less somewhat idealized than in courtly texts.